An intelligent photosensitive tracker for concentrating PV system - Jun Hu; Yachi, T. (2012 International Conference on Measurement, Information and Control, 2012)
The present paper describes the design of an intelligent photosensitive tracker, which is used to improve the efficiency of solar energy conversion by concentrating photovoltaic systems. The photosensitive sensor outputs a real-time signal sampled by multi solar cells. These signals are used to evaluate the light intensity and to realize the tracking function. Two operating modes (photosensitive sensor tracking and timed tracking) and a wake-up function are designed into the system. Four separate photosensitive quadrants cross-collect signals in real time. The system compares these signals and sends control commands using a microcontroller to drive two stepping motors to control the attitude of the solar cells. Based on light intensity detection, the center solar cell controls switching between operating modes. Finally, a system sensitivity test and a comparison test of power generation between a solar cell using this intelligent photosensitive tracker and another fixed facing south at an elevation angle of 45° are conducted. The performance of the cell using the intelligent photosensitive tracker is better, and the converted solar energy is increased by up to 34.77%.